Memantine for dementia. - Mcshane, R; Areosa Sastre, A; Minakaran, N (2006)
BACKGROUND: Memantine, a low affinity antagonist to glutamate NMDA receptors, may prevent excitatory neurotoxicity in dementia. OBJECTIVES: To determine efficacy and safety of memantine for people with Alzheimer's disease (AD), vascular (VD) and mixed dementia. SEARCH STRATEGY: The Specialized Register of the Cochrane Dementia and Cognitive Improvement Group was searched on 8th February 2006. This register contains references from all major healthcare databases and many ongoing trial databases and is updated regularly. In addition, the search engines Copernic and Google were used to identify unpublished trials through inspection of the websites of licensing bodies like the FDA , EMEA and NICE and of companies' websites (Lundbeck, Merz, Forest, Suntori etc) and clinical trials registries. SELECTION CRITERIA: Double-blind, parallel group, placebo-controlled, randomized trials of memantine in people with dementia. DATA COLLECTION AND ANALYSIS: Data were pooled where possible. Intention-to-treat (ITT) and observed case (OC) analyses are reported. MAIN RESULTS: 1. Moderate to severe AD. Two out of three six month studies show a small beneficial effect of memantine. Pooled data indicate a beneficial effect at six months on cognition (2.97 points on the 100 point SIB, 95% CI 1.68 to 4.26, P < 0.00001), activities of daily living (1.27 points on the 54 point ADCS-ADLsev, 95% CI 0.44 to 2.09, P = 0.003) and behaviour (2.76 points on the 144 point NPI, 95% CI 0.88 to 4.63, P=0.004), supported by clinical impression of change (0.28 points on the 7 point CIBIC+, 95% CI 0.15 to 0.41, P < 0.0001).2. Mild to moderate AD. Pooled data from three unpublished studies indicate a marginal beneficial effect at six months on ITT cognition (0.99 points on the 70 point ADAS-Cog, 95% CI 0.21 to 1.78, P = 0.01) which was barely detectable clinically (0.13 CIBIC+ points, 95% CI 0.01 to 0.25, P = 0.03) but no effect on behaviour, activities of daily living or OC analysis of cognition.3. Mild to moderate vascular dementia. Pooled data from two six month studies indicated a small beneficial effect of memantine on cognition (1.85 ADAS-Cog points, 95% CI 0.88 to 2.83, P = 0.0002), and behaviour (0.84 95% CI 0.06 to 0.91, P = 0.03) but this was not supported by clinical global measures.4. Patients taking memantine were slightly less likely to develop agitation (134/1739, 7.7% versus 175/1873, 9.3% OR 0.78, 95% CI 0.61 to 0.99, P = 0.04). This effect was slightly larger, but still small, in moderate to severe AD (58/506 [12%] vs 88/499 [18%]; OR = 0.6, 95% CI 0.42 to 0.86, P = 0.005). There is no evidence either way about whether it has an effect on agitation which is already present.5. Memantine is well tolerated. AUTHORS' CONCLUSIONS: Memantine has a small beneficial effect at six months in moderate to severe AD. In patients with mild to moderate dementia, the small beneficial effect on cognition was not clinically detectable in those with vascular dementia and was detectable in those with AD. Memantine is well tolerated.